Nonlinear dynamic modeling of pneumatic nailing devices. Issue 2 (4th March 2019) - Nili Ahmadabadi, Z.; Guilbault, Raynald; Laville, Frédéric
ABSTRACT: This paper develops a mathematical modeling procedure for pneumatic nailing devices. The representation integrates all the operation phases composing the nailing process. The model accounts for the dynamics of the chamber pressures, the moving parts, the nonlinear interactions and impacts between the fixed and moving components, and includes the nail gun body and workpiece. All the system parameters integrated into the proposed model were established from experimental measurements. This model also integrates a nonlinear empirical formulation to predict the nail penetration resistance force. The final representation is validated through a comparison of the predicted piston motion and air pressures to experimental measurements made on a specific nail gun. The average of the percent error established at important time positions is lower than 7%.